2002
DOI: 10.1302/0301-620x.84b5.0840712
|View full text |Cite
|
Sign up to set email alerts
|

Total vertebrectomy for primary malignant tumours of the spine

Abstract: Primary malignant tumours should be resected with wide margins. This may be difficult to apply to lesions of the spine. We undertook total vertebrectomy on seven patients, four males and three females with a mean age at operation of 26.5 years (6.3 to 45.8). The mean follow-up was 52.3 months. Histological examination revealed a Ewing's sarcoma in two patients and osteosarcoma, leiomyosarcoma, spindle-cell sarcoma, chondrosarcoma and malignant schwannoma in one each. In five patients, histological examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 17 publications
2
40
0
2
Order By: Relevance
“…This study agrees with previous investigations [2,6,18,21,24,32,34,38] supporting en bloc spondylectomy for treatment of primary malignant vertebral bone tumors and solitary spinal metastasis of certain tumor entities. En bloc spondylectomy followed by dorsoventral reconstruction allowed radical resections with negative margins in all patients.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This study agrees with previous investigations [2,6,18,21,24,32,34,38] supporting en bloc spondylectomy for treatment of primary malignant vertebral bone tumors and solitary spinal metastasis of certain tumor entities. En bloc spondylectomy followed by dorsoventral reconstruction allowed radical resections with negative margins in all patients.…”
Section: Resultssupporting
confidence: 92%
“…Nevertheless, intralesional surgery predisposes the patient to local recurrences and poor prognosis. To reduce the surgery-induced tumor cell dissemination, decrease local recurrence rates and to improve survival times, different techniques [8,15,16,20,23,25,26,32] for wide resections at the spine, involving either en bloc total [32] or hemilaminectomy [18] followed by en bloc corporectomy and dorso-ventral stabilization have been developed. In early 1980, Stener and Roy-Camille were the first to describe en bloc spondylectomy via a posterior approach after complete resection of the dorsal vertebral structures, i.e., both laminae, spinous process and parts of the pedicles, resulting in an oncological adequate resection for primary bone tumor locations not extending beyond the vertebral body [23,26].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, an increasing number of surgeons have performed and modified this procedure in order to apply the principles of tumor surgery [8] to the spine: attain wide resections, achieve long term local and systemic tumor control. The previously described techniques were modified [7,32,37,58,59], prognostic surgical scores [56,57,60,61] were established considering the underlying tumor biology, the number/presence of extraspinal metastases and an estimation of life expectancy. With the results of these scores and the tremendous advance in spine surgery technique the indication from primary spinal tumors is now extended to selected cases of solitary spinal metastases with biologically favorable tumor entities [1,54,62,70].…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative treatment, en bloc spondylectomy of spinal malignancies has attracted growing interest. It circumvents direct exposure of the tumor tissue and enables the surgeon to reach wide resection margins of the spine [8,18,20,32,35,46,48,51,52,[58][59][60]70]. For selected patients, the en bloc resection is expected to decrease local recurrence rates and improve the patient's chances of overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…In a later publication Tomita et al reported on five patients with primary malignant tumors of the spine [23]. Further authors adopted and modified these techniques and published their results with series of between seven and 29 patients [2,3,8,10,11].…”
Section: Introductionmentioning
confidence: 99%